METHOD OF DRINKING WATER PURIFICATION FROM NITRATE-IONS - Сененко, Н. Б.; Стороженко, Д. О.; Сененко, А. І.; Писаренко, П. В.; Степаненков, Г. В. (Scientific Progress & Innovations, 2014)
The chemical composition of the sample clay raw material is specified. The results of experimental research of sorption characteristics of clay raw material in the air - dry condition and thermally treated at different regimes concerning nitrate – ions are presented. The basic physical - chemical indices of natural drinking water quality are researched before and after treating by selected sorbent and desorption characteristics is defined. The possibility of reducing the concentration of nitrate - ions in water is shown up. The recommendations for purification of natural drinking water from nitrate – ions are developed.